The origins and traditions of the information policy in Russia - Evgeny Alfeevich Markov (Сравнительная политика, 2018)
For a long time the activities of mass media in Russia have been largely determined, and are still being determined now, by the state authorities. The state controls the activities of the information impact subjects, considering information resources, on an equal basis with other resources, to be important links that connect the multinational people into a single unity, and to remain one of the sources of the strength and power of the country.The author of the article, showing the changes that have taken place in the interaction between the state authorities and the media during three centuries of Russian history, expresses the idea of the inevitability of the active presence and control of the government institutions of the communicative and information field of the country, being an important factor ensuring the development of Russia, which conducts an independent external and internal policy and protects not only its national interests, but also the interests of a number of other countries.